A systems approach identifies time-dependent associations of multimorbidities with pancreatic cancer risk - Gomez-Rubio, Paulina; Michalski, Christoph (Annals of oncology, 2017)
AbstractBackground. Pancreatic ductal adenocarcinoma (PDAC) is usually diagnosed in late adulthood; therefore, many patients suffer or have suffered from other
Gesehen am 04.10.2018